AKTIVITAS EKONOMI MANTAN PEKERJA SEKS KOMERSIAL PASCA REHABILITASI DI KOTA PADANG - Sari, Ria Purnama (Pendidikan Sosiologi, 2014)
Economic activity is symptomatic of how the way people or communities meet their basic needs, to services and goods move, the way the question here relates to all the activities of people and communities associated with the production, distribution, exchange of services, goods consumption that does not violate the values and norms that exist in society. But in fact the community meet their needs in ways that became one of the PSK as a job to make ends meet. Government of West Sumatra establish rehab especially for the PSK PSKW Andam Dewi, the prostitute who was arrested and brought to the shelter will run until the rehabilitation period of time as determined by the institution, what post- rehabilitation work done by former prostitutes, especially coming from a former prostitute Padang. This study aimed to describe the economic activities carried out by the post-rehabilitation of former sex workers, describe the income and expenditure post-rehabilitation of fomer sex workers.This study uses the theory of action developed by Talcott Parson, using a qualitative approach with descriptive type. Informants in this study were drawn based on the number of informants Snowball Sampling 5 people. The type of data in this study are in the form of primary data and secondary data. The data collection techniques in this study in the form of in-depth interviews, observation and document study. The unit of analysis of data in this study is an individual, the post-rehabilitation of former sex workers in PSKW Andam Dewi Solok derived from Padang who were traders and sewing. The data analysis performed in this study are: One, noted that generate field notes, second, to collect and sort out, classify and create the index, and the third, to think that the data categories of data has meaning.The study found that post-rehabilitation of former sex workers need time to adapt back to society, as a former prostitute ashamed that former prostitutes locked himself at home, until finally former sex workers start their economic activities such as trading and sewing. Revenue earned from economic activity has been undertaken to meet the needs of everyday life. As a former sex workers have been able to finance the needs of food, rent, electricity, water and childrens education expenses.